Rendu-Osler-Weber syndrome: dermatological approach - Aline Blanco Barbosa; Günter Hans Filho; Carolina Faria dos Santos Vicari; Marcelo Zanolli Medeiros; Daíne Vargas Couto; Luiz Carlos Takita (Sociedade Brasileira de Dermatologia, 2015)
AbstractThe Rendu-Osler-Weber syndrome is a rare systemic fibrovascular dysplasia, recognized by mucocutaneous telangiectasias, arteriovenous malformations, epistaxis and family history. Recurrent bleeding, hypoxemia, congestive heart failure, portosystemic encephalopathy, and symptoms related to angiodysplasia of the central nervous system may occur. Since the treatment is based on supportive measures, early recognition is of utmost importance. This article reports the case of a 53-year-old male patient who presented telangiectasias on fingers, oral cavity and nasal mucosa for 10 years, with a history of recurrent epistaxis of varying severity since childhood. Mother, sister and daughter have similar lesions.